Phosphine-mediated synthesis of 1,4-oxazepine- and 1,5-oxazocine-based sugar hybrids from deoxysugar azides - Kurhade, Suresh E.; Salunkhe, Videsh T.; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2011)
An efficient and convenient method was developed for the synthesis of novel 1,4-oxazepine- and 1,5-oxazocine-based sugar hybrids from readily available deoxysugar azides by means of tributylphosphine-mediated tandem reactions. The resulting glycoconjugates might be useful in increasing the diversity of sugar backbones, and could find applications as potential glycomimetics and in drug discovery.
Keywords: Alkynes; azides; carbohydrates; heterocycles; oxazepines; oxazocines; Tandem reactions

Synthesis of novel dihydrooxazine and oxazoline based sugar hybrids from sugar azides - Kurhade, Suresh E.; Ravula, Sudhir; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Tetrahedron Letters, 2011)
A convenient one-step method for the synthesis of novel dihydrooxazine and oxazoline based sugar hybrids is reported starting from the readily accessible sugar azides and aldehydes. We have used Aube's protocol to achieve this transformation. The resulting glycoconjugates could be used to increase the diversity on the sugar backbone and may find applications as potential glycomimetics and in drug discovery. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dihydrooxazine; Glycoconjugate; Hydroxy azide; Oxazoline; Sugar azide; Sugar hybrids

Total synthesis of isofregenedadiol - Kurhade, Suresh E.; Sanchawala, Abbas I.; Ravikumar, Velayutham; Bhuniya, Debnath; Reddy, D. Srinivasa (Organic Letters, 2011)
The first total synthesis of isofregenedadiol, a bicyclic diterpene isolated from H. Viscosum, is reported starting from a D-(-)-pantolactone chiral pool. A one-pot quadruple reaction sequence comprising an enyne ring-closing metathesis/cross-metathesis/Diels-Alder/aromatization for the construction of a target skeleton Is the highlight of the present synthesis.

Synthesis of a sex pheromone of the longtailed mealybug, pseudococcus longispinus - Kurhade, Suresh E.; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2013)
The synthesis of a recently identified and highly active sex pheromone of the longtailed mealybug, Pseudococcus longispinus is reported. A concise synthetic route, use of the under explored Meyer-Schuster rearrangement, Claisen rearrangement, and ring-closing metathesis are the highlights of this work.
Keywords: Acylation; Metathesis; pheromones; rearrangement; Total synthesis